Body talk on social network sites and body dissatisfaction among college students: The mediating roles of appearance ideals internalization and appearance comparison - Yuhui Wang; Jingyu Geng; Ke Di; Xiaoyuan Chu; Li Lei (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2022)
The present study investigated the association between body talk on social networking sites (SNS) and body dissatisfaction as well as the mediating effects of appearance ideals internalization and appearance comparison in this relationship. Participants were 476 Chinese college students who completed questionnaires regarding SNS body talk, thin-ideal internalization, muscular-ideal internalization, general attractiveness internalization, appearance comparison, and body dissatisfaction. Results indicated that SNS body talk was positively linked to body dissatisfaction. The relationship between SNS body talk and body dissatisfaction was mediated by thin-ideal internalization and muscular-ideal internalization while the mediating effects of general attractiveness internalization and appearance comparison in this relationship were nonsignificant. Moderated mediation analysis further revealed that thin-ideal internalization mediated the association for women but not men and that other indirect effects did not differ among genders. The findings of this study provide more insights into the relationship between SNS use and body image.